2022
DOI: 10.1186/s40643-022-00565-9
|View full text |Cite
|
Sign up to set email alerts
|

Micronization using combined alkaline protease hydrolysis and high-speed shearing homogenization for improving the functional properties of soy protein isolates

Abstract: The present study aimed to investigate the functional properties of soybean protein isolate (SPI) treated with alkaline protease and high-speed shearing homogenization. Alkaline protease-hydrolyzed SPIs that were characterized by varying degrees of hydrolysis between 0 and 6% were treated with high-speed shearing homogenization to obtain different micro-particulate proteins. The results showed that this combined treatment could significantly reduce the particle size of SPI by markedly degrading the structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Both the foaming and the emulsifying activities of PPI were improved after enzymatic treatments at below 6% DH. Hao et al (2022) observed a similar trend for alkaline protease-hydrolyzed SPI at selected DH (1%-6%). The influence of bromelain, pepsin, and trypsin proteases on the structure of SPI-gum Arabic complexes demonstrated that the complex of pepsintreated SPI (especially protein treated for 3 h) and gum Arabic exhibited a stable emulsion with high solubility, uniform PSD, absolute charge value, and antioxidant properties .…”
Section: Hydrolysissupporting
confidence: 65%
“…Both the foaming and the emulsifying activities of PPI were improved after enzymatic treatments at below 6% DH. Hao et al (2022) observed a similar trend for alkaline protease-hydrolyzed SPI at selected DH (1%-6%). The influence of bromelain, pepsin, and trypsin proteases on the structure of SPI-gum Arabic complexes demonstrated that the complex of pepsintreated SPI (especially protein treated for 3 h) and gum Arabic exhibited a stable emulsion with high solubility, uniform PSD, absolute charge value, and antioxidant properties .…”
Section: Hydrolysissupporting
confidence: 65%
“…Yeast protein showed the average particle size (D50) of 12.80 μm with 3.71 μm D10 and 24.80 μm of D90. Enzyme treatment of yeast protein gave a decrease in the D50 value, which is generally observed from the hydrolysates of food proteins (Cui et al, 2021;Hao et al, 2022). The reduction in the protein sizes after enzymatic hydrolysis might be attributed to the disruption of protein structure, allowing smaller peptides to be more readily solubilized in the solution, thus correlating with an increase in peptide solubilities.…”
Section: Effects Of Hydrolysis On the Particle Sizementioning
confidence: 84%
“…Also, the limited particle size reduction (i.e. sizes in the μm range) could be attributed to the extent and duration of hydrolysis, which can lead to either further breakdown or aggregation of particles ( Hao et al, 2022 ; Shen et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…When soybean protein isolate (SPI) was treated with alkaline protease accompanied by high-speed shearing homogenization, it significantly improved the emulsion stability of the SPI hydrolysates. As a result, the foaming properties of SPI were improved significantly ( Hao et al, 2022 ). Recent studies have examined methods to use microbial proteases from a variety of sources to improve the chemical and physical properties of animal ( Ai et al, 2019 ; Du et al, 2022 ) and plant proteins ( Zhang Q. et al, 2021 ; Lin et al, 2022 ; Liu Y. Q. et al, 2022 ; Ren and Li, 2022 ; Wang T. et al, 2022 ; Hariharan et al, 2023 ; Lv et al, 2023 ; Vogelsang-O’Dwyer et al, 2023 ).…”
Section: Application Of Microbial Proteasesmentioning
confidence: 99%